Tip timing techniques for turbomachinery HCF condition monitoring - Ivey, P. C.; Grant, K. R.; Lawson, Craig P. (University of Cambridge, 2002)
High Cycle Fatigue (HCF) has been established as the major common failure mode in the US Air Force large fleet of aero-engines. Corrective measures for this failure mode in themselves deliver additional technical, managerial and cost pressures. Two responses are in place to address this problem; risk mitigation through accelerated engine development fixes and technology transition through targeted and focussed R&D studies. It is the latter that is of interests and is discussed in this paper. Aero-engine blade vibrations of sufficient amplitude cause High Cycle Fatigue, which reduces blade life. In order to observe this vibration a non-intrusive monitoring system is sought. The vibration can be detected by measuring blade tip timing since in the presence of vibration the blade timing will differ slightly from the passing time calculated from rotor speed. Work done to investigate the suitability of a commercially available capacitance probe tip clearance measurement system for application as a non-intrusive turbomachinery blade tip timing measurement device is reported. Capacitance probe results are correlated with simultaneously measure strain gauge results and the performance of the capacitance system in measuring blade vibration is analysed. The growing interest in blade high cycle fatigue within the aerospace industry, and an approach to monitoring their condition are discussed as an extension to the above study. The suggested approach is based upon the tip-timing method, using non-contact optical probes located around the engine’s casing. Two current tip-timing techniques are suggested for the purpose. The techniques are summarised, the experimental validation of both methods outlined, and the approach taken to investigate the potential use as a condition monitoring tool described. The paper is concluded with a discussion of the future use of tiptiming as a condition monitoring tool.